2020
DOI: 10.1177/0003134820964226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Evolving Morbidity of Omentoplasty for Perforated Peptic Ulcer Disease

Abstract: Mortality for perforated peptic ulcer (PPU) surgery ranges from 2-22% with morbidity ranging from 15-45%. Traditionally, these had been repaired with vagotomy and antrectomy or pyloroplasty with smaller perforations repaired with an omentoplasty. Laparoscopic repair has become increasingly prevalent and demonstrated to have shorter length of stay (LOS) and fewer complications. We are evaluating the surgical repair of PPU with omentoplasty to determine trends of utilization and surgical outcomes. We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Subsequently, 1466 records were screened; of them, 48 studies were assessed for eligibility against the inclusion/exclusion criteria. However, 9 articles were excluded owing to a lack of primary outcomes, 19,20 lack of access to a full article, 21,22 recruiting specific populations (elderly and pediatrics), 23 article retraction, 24,25 and article writing in a nonEnglish language. 26,27 Concomitantly, 6 articles were identified from the bibliographies of the screened articles, and all those studies were included.…”
Section: Results Of the Search Processmentioning
confidence: 99%
“…Subsequently, 1466 records were screened; of them, 48 studies were assessed for eligibility against the inclusion/exclusion criteria. However, 9 articles were excluded owing to a lack of primary outcomes, 19,20 lack of access to a full article, 21,22 recruiting specific populations (elderly and pediatrics), 23 article retraction, 24,25 and article writing in a nonEnglish language. 26,27 Concomitantly, 6 articles were identified from the bibliographies of the screened articles, and all those studies were included.…”
Section: Results Of the Search Processmentioning
confidence: 99%
“…Of the 29 studies included, there were 9 studies that did not have open conversion, 9,22,25,[28][29][30]36,42,43 12 studies that were analyzed with intention-to-treat analysis, 23,31,32,34,35,[38][39][40][44][45][46][47] 2 studies analyzed with per-protocol analysis, 26,33 3 studies that separately analyzed LOPR with open conversion, 27,37,41 1 study that did not mention whether studies were analyzed based on intention-to-treat or per-protocol analysis, 24 1 study that excluded open conversions in their analysis, 49 and 1 study that did not report on open conversion. 48 For the three studies that analyzed LOPR with open conversion separately, 27,37,41 we analyzed them using per-protocol analysis. Risk of bias assessments for RCTs and NRCTs are summarized in Supplementary Figure S1A and Figure S1B, respectively, http://links.lww.com/TA/C739.…”
Section: Resultsmentioning
confidence: 99%
“…Peptic ulcer perforation is one of the most serious surgical complications that can lead to death. Mortality from PUP surgery ranges from 2 to 22% and contributes to 37% of all peptic ulcer-related deaths [ 6 ]. Imhof's study on 108 patients with duodenal ulcer perforation showed that these patients had a poor prognosis, with mortality rates after 1 month, 1 year, and 5 years of 9.1%, 20.2% and 32.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] If newer methods affect the outcome of treatment, should surgery be indicated ? And [ 6 ] Should laparoscopic surgery be indicated? Some methods are used, such as simple perforation sutures, that can suture the PUP and cover it with the omentum (Cellan-Jones repair) or with Graham patches [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation